2014
DOI: 10.1080/15017419.2014.941923
|View full text |Cite
|
Sign up to set email alerts
|

Staff experiences of participation in everyday life of older people with intellectual disability who live in group homes

Abstract: This article aims to explore ways in which members of staff in group homes for people with intellectual disability experience participation, and what participation means for older people with intellectual disability. Qualitative interviews were performed with 15 members of staff at group homes in Sweden. The findings of this study are illustrated by considering two interacting themes and six subthemes. These involve staff experiences of the meaning of participation and factors which facilitate or inhibit it. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 37 publications
8
17
0
Order By: Relevance
“…Yes, it is absolutely true, and we have experienced staff around adults with PIMD. Another condition for participation that emerged in the interviews is that the organisation needs to be supportive and adequate, which is consistent with the findings reported by Kåhlin et al (2014). (Manager 3) individual characteristics that inhibit participation, as described by Kåhlin et al (2014), were also found in the present study; however, Kåhlin et al's finding that an inhibiting factor for participation was limited social contacts outside the group home was not brought up by the managers or staff members in the interviews in the present study.…”
Section: The Organisationsupporting
confidence: 86%
“…Yes, it is absolutely true, and we have experienced staff around adults with PIMD. Another condition for participation that emerged in the interviews is that the organisation needs to be supportive and adequate, which is consistent with the findings reported by Kåhlin et al (2014). (Manager 3) individual characteristics that inhibit participation, as described by Kåhlin et al (2014), were also found in the present study; however, Kåhlin et al's finding that an inhibiting factor for participation was limited social contacts outside the group home was not brought up by the managers or staff members in the interviews in the present study.…”
Section: The Organisationsupporting
confidence: 86%
“…We therefore argue that discussions on occupational justice (36-37) for older people with ID need to be influenced by a life course perspective (see for example [54][55]59). This study, and others (22,38), could inform such a discussion. The life course perspective regards ageing as a dynamic process brought about by an interaction between individual, social and historical factors over time (59).…”
Section: Discussionmentioning
confidence: 73%
“…The conditions for participation for older people with ID in everyday life and the community are thought to be closely related to contextual factors (22). Supportive social environments foster continuity, communion and a sense of coherence (23)(24)(25)(26), and arrangements in the physical environment, such as use of technical devices, can be vital for participation for this group of people (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations